2017
DOI: 10.1063/1.4985717
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of linear interfacial waves in a turbulent gas-liquid pipe flow

Abstract: The evolution of interfacial waves on a stratified flow was investigated experimentally for air-water flow in a horizontal pipe. Waves were introduced in the liquid level of stratified flow near the pipe entrance using an oscillating plate. The mean height of liquid layer and the fluctuations superimposed on this mean level were captured using high speed cameras. Digital image processing techniques were used to detect instantaneous interfaces along the pipe. The driving signal of the oscillating plate was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The main goal is to use this model to differentiate between linear and non-linear wave regimes in gas-liquid pipe flow. Note that the waves under investigation were purely wind-induced, i.e., they developed as result of gas-liquid interaction, as opposed to the mechanically induced waves described by Ayati et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal is to use this model to differentiate between linear and non-linear wave regimes in gas-liquid pipe flow. Note that the waves under investigation were purely wind-induced, i.e., they developed as result of gas-liquid interaction, as opposed to the mechanically induced waves described by Ayati et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the next generation of flow simulators are expected to include "regime-capturing" approaches which rely on finer grid resolution (Issa & Kempf, 2003;Carneiro et al, 2011;Danielson et al, 2012;Nieckele et al, 2011;Nieckele & Carneiro, 2017). Furthermore, recent developments in experimental investigation of this system (Birvalski et al, 2014(Birvalski et al, , 2015(Birvalski et al, , 2016Ayati et al, 2014Ayati et al, , 2015Ayati et al, , 2016Ayati et al, , 2017André & Bardet, 2017), have shown that the overall bulkflow is strongly coupled with wavy interface. To this end, detailed description of measured interfacial waves is expected to be of valuable use with respect to validation of models and CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The newly formed satellite interfaces increase drastically the exchange surface, enhancing the transfer between the two phases. Practical examples include oil spill mitigations (Gopalan & Katz 2010;Afshar-Mohajer et al 2018), oil and gas transportation from remote wells (Galinat et al 2005;Ayati et al 2017), air entrained by bow waves in naval applications (Baba 1969;Shakeri, Tavakolinejad & Duncan 2009), together with ocean-atmosphere interactions with breaking waves inducing bubble-mediated gas exchange (Deane & Stokes 2002;Deike, Lenain & Melville 2017;Deike & Melville 2018) and ejecting sea spray aerosols (Veron 2015).…”
mentioning
confidence: 99%
“…However, they do not provide insight on the phase-dependency of the flow structure. This can only be achieved by conducting phase-locked measurements (Ayati et al, 2017) or by performing conditional-averaging techniques on statistically independent velocity fields. The latter is the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%